The effect of different types of disclosure of obsessive-compulsive personality disorder on employers' hiring decision - Nor Hidayu Ahmad Jalaluddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Disclosing one's psychological disorder might have a significant effect on employers' selection decision, although this has not been fully and widely researched. Employers' reaction to job applicants who either explicitly or implicitly disclose to having personality disorders has not been studied before, even though research on disclosure of other types of psychological disorder in general have garnered mixed findings. Thus, this study aimed to investigate the effect of the different types of disclosure; implicit and explicit disclosure on employers' hiring decision, by focusing on Obsessive-Compulsive Personality Disorder (OCPD) as a constant variable. Implicit disclosure of OCPD was divided into two; positive information only and negative information only. As no previous study has been attempted to study managers' selection decisions of applicants with OCPD traits, therefore materials for this study were prepared by the researcher. Data was analysed using descriptive statistics, paired sample t-test and one-way within subjects ANOVA. Results showed that the hiring scores of participants towards hypothetical applicants representing the three different conditions differed significantly, F(1.67, 95.30) = 66.37, p <.05, with the hypothetical applicant who implicitly disclosed positive information about OCPD receiving the highest rating (Mean=1.58, SD= 0.649). The result also showed that explicitly disclosing a history of OCPD has a significant negative effect on participants' hiring decisions. Overall, this study highlighted the need for more research that looks into the influence of the type of information given about an applicant's mental condition on interviewers' selection decisions.